Studying Distribution Channel Patterns in the Poultry Farming Industry - Fina Ratna Sari; Sudarmiatin Sudarmiatin; Titis Shinta Dhewi (Profesional Muda Cendekia Publishing, 2022)
This study aims to explore, understand, and determine the role of distribution channels for Day Old Chicken and Day Old Duck hatchery industry players in Tulungagung Regency in managing their distribution channels. This research is important to do because this research will examine more deeply how to get distribution channels, how to manage distribution channels in marketing activities, and how to determine the right distribution channel strategy through SWOT analysis. This study aims to explore, understand, and determine the role of distribution channels for the Day Old Chicken and Day Old Duck hatchery industry players in Tulungagung Regency in managing their distribution channels. This research uses a qualitative approach and this type of research is a multi-case study. In this study, to obtain the validity of the data, triangulation was carried out. This research is qualitative research that uses SWOT analysis (Strengths, Weaknesses, Opportunities, and Threats) in analyzing and identifying data. The results show that the strategy adopted by the Poultry Hatchery Industry is a direct-distribution strategy, the direct distribution channel carried out by DOC and DOD has the main advantage in terms of cost, but there are also obstacles to further decline in sales targets. The results of the analysis found the cause of the decline in sales targets because the company did not fully implement direct distribution channels, one way to achieve this is by utilizing online marketing.